Hubungan Pengetahuan Keluarga Pasien Terhadap Kepatuhan Penggunaan Masker Di Era Pandemi Covid-19 Di Rsud Dr. Hasri Ainun Habibie Provinsi Gorontalo - Iskandar Simbala; Andi Nuraina Sudirman; Astria Cahyati Papeo; Ayu Sintia (Jurnal Rumpun Ilmu Kesehatan, 2021)
Covid-19 is a global epidemic that not yet ended and there are still significant additions of positive cases. Positive cases and death rates in Indonesia are increasing. Therefore efforts are needed to break the chain of Covid-19 spread. This research used a descriptive design with a cross sectional design. the results showed that knowledge with a good category was equal, adherence to using masks was equal , thus it can be concluded with the use of masks in the era of the covid-19 pandemic at the dr. Hasri Ainun Habibie. This research is expected to increase patient’s family compliance in the use of masks in the pandemic era.